2018
DOI: 10.1123/ijspp.2017-0434
|View full text |Cite
|
Sign up to set email alerts
|

The Preparation Period in Basketball: Training Load and Neuromuscular Adaptations

Abstract: The preparation period induced minimal changes in the CMJ, while the ability to sustain repeated COD efforts was improved. Reaching high session rating of perceived exertion training loads might partially and negatively affect the ability to produce strength and power.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(69 citation statements)
references
References 26 publications
(36 reference statements)
1
64
3
1
Order By: Relevance
“…The average of the best 3 values was used for analysis. Reliability and validity of this test have been widely reported in basketball literature [5,21,28].…”
Section: Design and Methodologymentioning
confidence: 90%
See 4 more Smart Citations
“…The average of the best 3 values was used for analysis. Reliability and validity of this test have been widely reported in basketball literature [5,21,28].…”
Section: Design and Methodologymentioning
confidence: 90%
“…Previous studies reported changes in physical fitness of basketball players to be affected by the competitive level of play [4][5][6][7]17]. Thus, a thorough understanding of seasonal fitness variations at varying playing standards might highlight useful information for physical preparation staff and coaches alike.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations